Alternating Current Heating Model of Rods Located in Siemens Reactor. Issue 1 (14th July 2020) - Yu, C.; Zhou, Y. M.; Du, P.; Zhao, L.; Zhao, D.; Wang, P. J.; Tian, L.; Xie, G.; Hou, Y. Q.
Abstract: The energy of a Siemens reduction furnace is provided by the current heating of silicon rods. Further, owing to the temperature gradient in the silicon rod, its center temperature is considerably higher than its surface temperature. The skin effect of alternating current (AC) reduces the temperature gradient within the silicon rod. Therefore, this study essentially establishes an AC heating model of 24 pairs of rod Siemens reactor based on electromagnetic theory. The calculation results are consistent with the industrial production data, indicating that the model is accurate. The results demonstrate that when the AC frequency exceeds 50 kHz, the current density at the center of the silicon rod becomes very small, tending to zero. As the frequency continues to increase, the area where the current density is close to zero expands; further, when the AC frequency exceeds 50 kHz, there exists a constant temperature zone near the central region of the silicon rod, and as the frequency of the AC increases, the range of the constant temperature zone gradually expands outward from the center of the silicon rod. The temperature difference inside the silicon rod increases with the reactor wall emissivity.